Clinical and economic analysis of drug costs in a general hospital in 2014-2018 - A. T. Burbello; A. S. Fedorenko; E. L. Latariya; M. V. Pokladova; K. A. Zagorodnikova (Фармакоэкономика)
Objectives. To study the structure of drug purchases by a general hospital considering the names and costs of the purchased drugs as well as their current consumption by various clinical departments.Materials and Methods. The drug consumption was analyzed using the ABC/VEN and ATC/DDD methods with a simultaneous analysis of case histories.Results. The analysis of drug purchases in 2014-2018 and the obtained results prompted a reassessment of the drug procurement policy and readjustment of the financial resources between various groups of drugs.Conclusion. The simultaneous use of the ABC/VEN and ATС/DDD analyzes and the reevaluation of the list of prescribed medications allowed us to propose the ways to optimize the structure of drug consumption in a typical hospital.